Nasal cytology and histology in CRSwNP: Two sides of the same coin - Gelardi, Matteo; Giancaspro, Rossana; Cassano, Michele; Ribatti, Domenico (Frontiers in Medicine, 2023)
Knowledge of chronic rhinosinusitis with nasal polyps (CRSwNP) has increased rapidly over the past decade. However, the study of the histological features of nasal polyps has not gone hand in hand with the study of the inflammatory mechanisms underlying CRSwNP. Indeed, precisely because they are benign neoformations, nasal polyps have not attracted the attention of pathologists over the years. Nasal cytology has shown that CRSwNP, generally defined as a Type-2 disease, is characterized not only by eosinophilic but also mast cell inflammation and, in particular, the most severe forms of CRSwNP are precisely characterized by a mixed eosinophilic-mast cell inflammation. Interestingly, mast cells cannot be visualized by histology due to limitations in staining and magnification, and therefore are not commonly described in histological reports of nasal polyps. However, immunohistochemistry can highlight these latter cells and specifically this technique has recently demonstrated that mast cells are located in the lamina propria of almost all types of polyps and in the epithelial level of the most severe forms. Unfortunately, the latter technique is not commonly carried out in clinical practice by virtue of the high cost and time burden. On the other hand, nasal cytology is an easy-to-apply and economic diagnostic tool, commonly practiced in rhinological setting, which can effectively fill the gap between histology and immunohistochemistry, allowing to non-invasively establish the endotype of nasal polyps and to highlight all cytotypes, including mast cells, that cannot be visualized by the other two techniques. The recent demonstration of the close correlation between mast cell intraepithelial infiltrate and CRSwNP severity paves the way for new therapeutic possibilities aimed at reducing not only eosinophilic infiltration but also mast cell infiltration.